2015
DOI: 10.1002/hon.2253
|View full text |Cite
|
Sign up to set email alerts
|

Induction, consolidation, and maintenance therapies with arsenic as a single agent for acute promyelocytic leukaemia in a 11‐year follow‐up

Abstract: The aim of this study was to evaluate the effect of arsenic trioxide as a single agent in acute promyelocytic leukaemia cases for induction, consolidation, and maintenance therapy in a long-term, 11-year follow-up. We studied 60 patients with acute promyelocytic leukaemia. Sixty percent of the patients were aged between 12 and 24 years. Arsenic trioxide was infused at a 0.15 mg/kg daily dose until complete remission was achieved. After 2 weeks of rest, arsenic trioxide was infused daily for 28 days as a consol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
7
0
2
Order By: Relevance
“…This finding was in line with recent reported data from current ATO‐based regimens have a t‐MN incidence of only 0% to 0.3% . Interestingly, Aznab M et al reported that there were no second malignancies including t‐MN during an 11‐year follow‐up for APL patients treated by ATO monotherapy . Thus, these results suggested that APL patients treated with ATO did not appear to have an excess risk of t‐MN.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was in line with recent reported data from current ATO‐based regimens have a t‐MN incidence of only 0% to 0.3% . Interestingly, Aznab M et al reported that there were no second malignancies including t‐MN during an 11‐year follow‐up for APL patients treated by ATO monotherapy . Thus, these results suggested that APL patients treated with ATO did not appear to have an excess risk of t‐MN.…”
Section: Discussionsupporting
confidence: 90%
“…One of them was relapsed before the epidemic began, it was resistant to therapy, and the patient died due to leukostasis. There were three cases of M3 Acute Promyelocytic leukemia which are receiving Arsenic and do not have any particular problems [11]. We had 12 cases of myeloma in this 90-day period.…”
Section: Resultsmentioning
confidence: 98%
“…Seweryn Mucha 1, 2 , Mateusz Berezowski 1, 2 , Katarzyna Markowska 1 * (Cephalon) stosowanego w leczeniu ostrej białaczki promielocytowej (APL -Acute Promyelocytic Leukemia) [3,27]. Aktualnie prowadzonych jest lub zakończono szereg badań klinicznych nad użytecznością arszeniku w leczeniu innych nowotworów krwi, jak również guzów litych [1,74].…”
Section: Mechanizmy Toksyczności I Transportu Arsenu U Mikroorganizmówunclassified
“…Związek ten posiada konformację podobną do glicerolu, dlatego też u wszystkich organizmów wnika do wnętrza komórki zgodnie z gradientem stężeń przez akwagliceroporyny. U bakterii Escherichia coli kanałem glicerolowym umożliwiającym przenikanie As(OH) 3 [56,95]. Badania wskazują również, że za akumulację kwasu arsenowego w komórkach S. cerevisiae może być także odpowiedzialny białkowy kompleks Fet3-Ftr1, umożliwiający transport żelaza [6].…”
Section: Sposoby Wnikania Arsenu Do Komórekunclassified